Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2001
DOI: 10.1145/365024.365061
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring perfect knowledge in-the-world for imperfect knowledge in-the-head

Abstract: Memory can be internal or external -knowledge in-theworld or knowledge in-the-head. Making needed information available in an interface may seem the perfect alternative to relying on imperfect memory. However, the rational analysis framework (Anderson, 1990) suggests that least-effort tradeoffs may lead to imperfect performance even when perfect knowledge in-the-world is readily available. The implications of rational analysis for interactive behavior are investigated in two experiments. In experiment 1 we var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 16 publications
(10 reference statements)
7
47
0
Order By: Relevance
“…The results suggest that, because it was so easy and fast to revisit slides in the LVM, being able to return to a slide with just one click, participants chose to do so instead of holding large amounts of diagnostic information in memory. This fits with existing research that suggests people adopt least-effort tradeoffs which mean they rely on imperfect 'knowledge in-the-head' (memory) when perfect 'knowledge in-the-world' (in this case, the information contained within the slides) requires effort to access [20], as is the case with the microscope; with the LVM it seems that the reduced effort to access the slides led to greater use of perfect 'knowledge in-the-world.' As such, we can hypothesise that use of this technology would decrease cognitive load and possibly pathologists' fatigue in long and complex cancer cases.…”
Section: Discussionsupporting
confidence: 86%
“…The results suggest that, because it was so easy and fast to revisit slides in the LVM, being able to return to a slide with just one click, participants chose to do so instead of holding large amounts of diagnostic information in memory. This fits with existing research that suggests people adopt least-effort tradeoffs which mean they rely on imperfect 'knowledge in-the-head' (memory) when perfect 'knowledge in-the-world' (in this case, the information contained within the slides) requires effort to access [20], as is the case with the microscope; with the LVM it seems that the reduced effort to access the slides led to greater use of perfect 'knowledge in-the-world.' As such, we can hypothesise that use of this technology would decrease cognitive load and possibly pathologists' fatigue in long and complex cancer cases.…”
Section: Discussionsupporting
confidence: 86%
“…The primary task was to program a VCR using a simulated VCR built in Macintosh Common Lisp. The VCR interface (see Figure 1) was not based on a commercially available VCR; rather, it was designed for experimental use (Gray, 2000;Gray & Fu, 2001). The interruption task was a pursuit-tracking task that required participants to track a moving target.…”
Section: Methodsmentioning
confidence: 99%
“…The path analysis showed that the overall strategy that participants adopted (perimeter vs. lawnmower) did not affect performance, but differences were apparent when the path data were analyzed at finer levels of detail. This led us to hypothesize that the walk group performed more perfect searches because: a) Walking increased participants' agility, which made it easier to deviate to targets and decoys (it is well known that small time differences in interaction cost can have a large impact on performance [Gray and Fu 2001]), or b) It was only when translational and rotational body-based information was provided that participants could accurately remember where they had (not) traveled (spatial updating [Loomis et al 1999]). …”
Section: Why Is It Difficult To Navigate In Virtual Worlds?mentioning
confidence: 99%